The Use of Disintegration Ratio in Evaluating Rock Durability in Selected Mudrock Samples in Indonesia - Misbahudin Misbahudin; Imam Achmad Sadisun (UIR PRESS, 2019)
Characterization of durability of mudrocks is important regarding its slaking behaviour within a short time when exposed to and or interact with water. Some relevant cases that occurred due to slaking are damage to roads and slope failures along the Cipularang and Cipali Toll Road. Current engineering activities related to the presence of mudrocks are being and will be held in several locations in Indonesia such as the construction of the Cisumdawu Toll Road in Ujungjaya District, Sumedang and building the National Observatory in Timau District, Kupang. This research is useful for providing engineering considerations related to those activities. The methods used in this research included X-ray diffraction to obtain mineralogy of mudrock, laboratory testing of physical properties of rocks such as dry density, water content, porosity, absorption and mudrocks durability tests. Durability of rocks was determined by disintegration index test. Testing was carried out by wetting and drying of rock samples. Test results showed that the average disintegration ratio of claystones, shales, mudstones and siltstones are 0.1035, 0.2183, 0.4942 and 0.9900. Slaking mode occurs to claystones, mudstones and shales is body slaking while dispersion slaking occurs to siltstones. Evaluation of the durability of mudrocks in this research indicates that siltstones have the highest durability characterized by very slow disintegration, followed by mudstones, shales and claystones at the lowest with very quick disintegration. Disintegration ratio from the disintegration index test characterizes the durability of mudrocks in more details. It can be concluded that porosity and absorption are incorporated into the main factors affecting the durability of mudrocks.